PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Patty, Maria Apriyane; Bura, Manggalawati Tande; Karubaba, Christine Jois (Politeknik Negeri Ambon, 2025)
Introduction: Firm value serves as a key indicator of a company’s ability to generate wealth for its shareholders and stakeholders. This study aims to analyse the effect of capital structure and profitability on firm value in Indonesian manufacturing companies. Methods: This quantitative research, employing an explanatory design, utilises the library method and panel data regression analysis, with a fixed effects model, on a sample of 85 manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period, resulting in 425 observations. Independent variables include capital structure proxied by the equity ratio, and profitability measured through return on assets and return on equity. In contrast, the dependent variable is firm value, represented by the price-to-book value and Tobin’s Q. Results: Research findings indicate that the equity ratio has a positive and significant effect on firm value, with a coefficient of 0.287 and a p-value of 0.001, supporting the trade-off theory. The return on assets shows a positive and significant effect, with a coefficient of 4.567 and a p-value of 0.000. In contrast, the return on equity demonstrates a positive and significant effect, with a coefficient of 2.145 and a p-value of 0.002. The research model has an R-squared of 0.7234, indicating that 72.34 % of firm value variation can be explained by capital structure and profitability. Conclusion: The findings confirm that capital structure optimisation and profitability enhancement through operational efficiency constitute fundamental strategies for creating firm value for stakeholders in Indonesia's manufacturing sector. Keywords: Capital Structure, Profitability, Firm Value, Manufacturing Companies, Indonesia Stock Exchange